Cell membrane camouflaged nanoparticles: a new biomimetic platform for cancer photothermal therapy - Wu M (Dove Medical Press, 2019)
Minliang Wu,1,* Wenjun Le,2,* Tianxiao Mei,2 Yuchong Wang,1 Bingdi Chen,2 Zhongmin Liu,2 Chunyu Xue11Department of Plastic Surgery,Changhai Hospital, Second Military Medical University, Shanghai 200433, People’s Republic of China; 2Institute for Regenerative Medicine and Translational Nanomedicine, Shanghai East Hospital, The Institute for Biomedical Engineering & Nano Science, Tongji University School of Medicine, Shanghai 200092, People’s Republic of China*These authors contributed equally to this work Abstract: Targeted drug delivery by nanoparticles (NPs) is an essential technique to achieve the ideal therapeutic effect for cancer. However, it requires large amounts of work to imitate the biomarkers on the surface of the cell membrane and cannot fully retain the bio-function and interactions among cells. Cell membranes have been studied to form biomimetic NPs to achieve functions like immune escape, targeted drug delivery, and immune modulation, which inherit the ability to interact with the in vivo environments. Currently, erythrocyte, leukocyte, mesenchymal stem cell, cancer cell and platelet have been applied in coating photothermal agents and anti-cancer drugs to achieve increased photothermal conversion efficiency and decreased side effects in cancer ablation. In this review, we discuss the recent development of cell membrane-coated NPs in the application of photothermal therapy and cancer targeting. The underlying biomarkers of cell membrane-coated nanoparticles (CMNPs) are discussed, and future research directions are suggested.Keywords: cell membrane, nanoparticles, photothermal therapy, cancer targeting